Transforming pre-operative fasting practice: A nurse-led liberal fluid fasting regimen - Jinseok Kim (Journal of Perioperative Nursing)
Introduction: Traditional pre-operative fasting practice often involves extended periods without fluids, and can be a source of discomfort and anxiety for patients. This can lead to negative experiences and potentially contribute to complications. Evidence suggests that these practices may not be necessary to minimise the risk of pulmonary aspiration during surgery. This quality improvement project implemented a nurse-led liberal fluid fasting regimen for pre-operative patients. The aim was to improve patient comfort and wellbeing while maintaining safety.